Health-related outcomes with supervised exercise and myofascial release versus only supervised exercise in subacromial pain syndrome: a randomized controlled single-blind study - Yongzhong Li; Xuan Li; Haixin Song; Yiqun Shou; Qian Fang (BMC, 2024)
Abstract Background Myofascial tissue plays a critical role in shoulder joint mobility disorders. Myofascial release therapy (MFR) is frequently utilized to restore the extensibility of fascial tissue and is considered beneficial for various clinical conditions such as low back pain and ankle injuries. However, no studies have yet evaluated the effects of MFR on periscapular muscles activation and shoulder mobility in patients with subacromial pain syndrome(SAPS). Objective The purpose of this study was to compare the effectiveness of MFR combined with supervised exercise(SE) and SE alone in patients with SAPS. Design Assessor-blinded randomized controlled trial. Setting Sir Run Run Shaw Hospital, Zhejiang University School of Medicine. Subjects Subacromial pain syndrome patients. Methods Fifty participants were divided into two groups: SE group and MFR + SE group, each group 25 cases. Both treatment methods were performed 5 times a week for 4 weeks. Main measures Shoulder pain severity was assessed by visual analog scale (VAS); shoulder range of motion (ROM) by a goniometer; functionality by shoulder Pain and Disability Index (SPADI); and periscapular muscles activation by sEMG. All measurements were evaluated both pre- and post-treatment. Results An ANOVA analysis indicated no significant group by time interactions for flexion ROM and resting VAS (p > 0.05). However, significant group by time interactions were found for SPADI, abduction and external rotation ROM, and activity VAS (p < 0.05). Post-hoc tests revealed significant improvements in SPADI, abduction and external rotation ROM, and activity VAS in both groups compared to pre-treatment (p < 0.05). Additionally, there were significant group by time interactions for the sEMG values of the upper trapezius and serratus anterior (p < 0.05). Post-hoc tests showed that compared to pre-treatment, the MFR + SE group had decreased upper trapezius sEMG values and increased serratus anterior sEMG values(p < 0.05), while the SE group showed increased serratus anterior sEMG values(p < 0.05). After the 4-week intervention, there were significant between-group differences in SPADI, abduction and external rotation ROM, activity VAS, and sEMG values of the upper trapezius and serratus anterior(p < 0.05). Conclusion Four weeks of MFR combined with SE can increase shoulder ROM, improve pain, and thus enhancing functional activities in patients with SAPS. Additionally, it can further improve the balance between the upper trapezius and serratus anterior to improve the dynamics of the periscapular muscles. Trial registry number ChiCTR2200061054. Date of registration 15/06/2022.